Foliar herbivory by caterpillars and aphids differentially affects phytohormonal signalling in roots and plant defence to a root herbivore. (10th January 2020) - Karssemeijer, Peter N.; Reichelt, Michael; Gershenzon, Jonathan; van Loon, Joop; Dicke, Marcel
Abstract: Plant‐mediated interactions are an important force in insect ecology. Through such interactions, herbivores feeding on leaves can affect root feeders. However, the mechanisms regulating the effects of above‐ground herbivory on below‐ground herbivores are poorly understood. Here, we investigated the performance of cabbage root fly larvae ( Delia radicum ) on cabbage plants ( Brassica oleracea ) previously exposed to above ground herbivores belonging to two feeding guilds: leaf chewing diamondback moth caterpillars ( Plutella xylostella ) or phloem‐feeding cabbage aphids ( Brevicoryne brassicae ). Our study focusses on root‐herbivore performance and defence signalling in primary roots by quantifying phytohormones and gene expression. We show that leaf herbivory by caterpillars, but not by aphids, strongly attenuates root herbivore performance. Above‐ground herbivory causes changes in primary roots in terms of gene transcripts and metabolites involved in plant defence. Feeding by below‐ground herbivores strongly induces the jasmonate pathway in primary roots. Caterpillars feeding on leaves cause a slight induction of the primary root jasmonate pathway and interact with plant defence signalling in response to root herbivores. In conclusion, feeding by a leaf chewer and a phloem feeder differentially affects root‐herbivore performance, root‐herbivore‐induced phytohormonal signalling, and secondary metabolites. Abstract : Caterpillars (Plutella xylostella) and aphids (Brevicoryne brassicae) feeding on leaves of Brassica oleracea differentially affect gene expression, phytohormone concentrations and defence against cabbage root fly larvae (Delia radicum) in the primary root.